2015
DOI: 10.1128/cvi.00034-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Feline Leukemia Virus (FeLV) Inactivated Whole-Virus Vaccine and Canarypox Virus-Vectored Vaccine during Virulent FeLV Challenge and Immunosuppression

Abstract: Four vaccines for feline leukemia virus (FeLV) are available in the United States. This study's purpose was to compare the efficacy of Nobivac feline 2-FeLV (an inactivated, adjuvanted whole-virus vaccine) and PureVax recombinant FeLV (a live, canarypox virus-vectored vaccine) following FeLV challenge. Cats were vaccinated at 9 and 12 weeks with Nobivac feline 2-FeLV (group A, n = 11) or PureVax recombinant FeLV (group B, n = 10). Group C (n = 11) comprised unvaccinated controls. At 3 months postvaccination, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Another advantage is that FeLV vaccines released in U.S. in 1990–1991 were inactivated (i.e., killed) whole virus vaccines [ 25 , 26 ] which set a precedent of inactivated virus vaccine for future feline retroviral vaccines. In fact, the inactivated whole FeLV vaccine (Nobivac ® FeLV) was more effective than the recombinant canarypox virus vectored FeLV vaccine (Purevax ® FeLV) [ 27 ]. In addition, the long-term use of the inactivated whole FeLV vaccine demonstrated that this vaccine can be safely used in pet cats without any known incidence of FeLV infection from vaccine virus [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage is that FeLV vaccines released in U.S. in 1990–1991 were inactivated (i.e., killed) whole virus vaccines [ 25 , 26 ] which set a precedent of inactivated virus vaccine for future feline retroviral vaccines. In fact, the inactivated whole FeLV vaccine (Nobivac ® FeLV) was more effective than the recombinant canarypox virus vectored FeLV vaccine (Purevax ® FeLV) [ 27 ]. In addition, the long-term use of the inactivated whole FeLV vaccine demonstrated that this vaccine can be safely used in pet cats without any known incidence of FeLV infection from vaccine virus [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using other routes of infection than the oro-nasal route or the concurrent administration of corticosteroids may introduce a bias in the assessment of vaccine efficacy. Although an oro-nasal challenge with a virulent FeLV strain is feasible as shown in our study, the intraperitoneal route or the simultaneous administration of glucocorticoids has frequently been used to increase the efficiency of FeLV challenge [20,24,28]. However, the route of infection may have an impact on the outcome of an infectious challenge and consequently on the efficacy of a vaccine candidate.…”
Section: Discussionmentioning
confidence: 83%
“…Efficacy data have been published for the different types of vaccines but few comparative studies are available [20]. In addition, most of the published studies rely on artificial challenge models, using the intra-peritoneal route or high doses of challenge virus with simultaneous administration of glucocorticoids [24]. Although less commonly performed, natural challenge models of infection are generally regarded as the most valuable method of assessing FeLV vaccine efficacy, mimicking natural infection as much as possible.…”
Section: Introductionmentioning
confidence: 99%
“…e read with interest the paper on the comparative efficacy of feline leukemia virus (FeLV) inactivated whole-virus vaccine and canarypox virus-vectored vaccine during virulent FeLV challenge and immunosuppression by Patel et al (1).…”
mentioning
confidence: 99%